The Efficacy of Seluang Fish Oil (Rasbora agrotynea) Related Body Weight, Lipid Profile, Adiponectin and Leptin in Wistar Rats-Induced High Fat Diet - Fatmawati Karim; Rachmat Hidayat; Erizka Rivani; Husnul Khotimah; Ester G Pansserga (HM Publisher, 2018)
Background Rasbora agrotynea (local name : Seluang ) is a fish native to Sumatera, Malaya and Borneo. This fish has a potential as a local wisdom for supplementation of omega 3 and omega 6. In Sumatera, Seluang fish was used as traditional food. Aim of Study Aim of this study to explore the efficacy of seluang fish oil in body weight, lipid profile, adiponectin and leptin level in Wistar Rats-Induced High Fat Diet Methods This study was an experimental study , pre-post test with control group design. The sample in this study was 30 male rats, 8 weeks old, weight 150-200 gram. Rats were given high fat diet and seluang fish oil at dose of 0,1 , 0,2 and 0,4 mL/200 gr BW/day for 2 weeks. Seluang fish oil was extracted by distilation methods. The results of this study were assayed by SPSS 18. Results Seluang fish oil 0,4 mL/200 gr BW was more potent to reduce body weight gain, triglyseride level, leptin and increase adiponectin level than seluang fish oil 0,1 mL/200 gr BW, 0,2 mL/200 gr BW, negative control and positive control. Conclusion Seluang fish oil had a potention to reduce body weight, triglyceride, leptin and increase adiponectin level. Keywords: Seluang fish Oil – body weight- triglyserida – leptin - adiponectin